Dari A-Politis menjadi Ekklesia Politis: Rekonstruksi Pendidikan Kristiani melalui Konsep “Gereja dan Reformasi” Eka Darmaputera - Listia Wangania, Judith Debora (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2026)
Abstract. This article examines the church's identity crisis in Indonesia, manifested in its apolitical stance. This problem stems from the legacy of theological dualism that separates the spiritual and secular realms, reinforced by a model of Christian education that emphasizes solely individualistic salvation. This paper attempts to reconstruct Christian education to transform it into a political ecclesia, a church with responsible prophetic awareness and involvement in the nation's public and political affairs. This study employs a literature review method, incorporating Eka Darmaputera's key concept of "Church and Reformation" (Ecclesia Semper Reformanda). The result indicates that Christian education needs to be radically reconstructed into a prophetic school that adopts critical pedagogy. This reconstruction demands changes to the normative curriculum, which instills ethical-political awareness, forming a community that is critical, courageous, and responsible for issues of social justice, human rights, and the integrity of creation.Abstrak. Artikel ini membahas krisis identitas gereja di Indonesia yang terwujud dalam sikap a-politis. Permasalahan ini berakar dari warisan dualisme teologis yang memisahkan ranah spiritual dan sekuler, diperkuat oleh model Pendidikan Kristiani yang menekankan keselamatan individualistik semata. Tulisan ini berupaya merekonstruksi Pendidikan Kristiani agar bertransformasi menjadi Ekklesia Politis, yakni gereja yang memiliki kesadaran dan keterlibatan profetik yang bertanggung jawab dalam urusan publik dan politik negara. Kajian ini menggunakan metode studi pustaka dengan menggunakan konsep kunci Eka Darmaputera “Gereja dan Reformasi” (Ecclesia Semper Reformanda). Hasil penelitian menunjukkan bahwa Pendidikan Kristiani perlu direkonstruksi secara radikal menjadi sebuah sekolah kenabian yang mengadopsi pedagogi kritis. Rekonstruksi ini menuntut perubahan kurikulum normatif, yang menanamkan kesadaran etis-politik, membentuk umat yang kritis, berani, dan bertanggung jawab terhadap isu keadilan sosial, hak asasi manusia, dan keutuhan ciptaan.